2000
DOI: 10.1590/s0103-90162000000300005
|View full text |Cite
|
Sign up to set email alerts
|

Atividade ovicida de extratos aquosos de meliáceas sobre a mosca branca Bemisia tabaci (Gennadius) biótipo B em tomateiro

Abstract: RESUMO: A mosca branca Bemisia tabaci (Gennadius) biótipo B atualmente é uma das principais pragas do tomateiro. O uso de extratos botânicos no controle desse inseto é uma alternativa promissora, mas que ainda precisa ser melhor pesquisada. O presente trabalho teve como objetivo determinar a bioatividade de extratos aquosos de folhas de Melia azedarach L. e de ramos de Trichilia pallida Swartz, sobre a mosca branca Bemisia tabaci (Gennadius) biótipo B, criada em tomateiro. Foram realizados dois experimentos, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
20

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
1
6
0
20
Order By: Relevance
“…The mortality percentages obtained with the extracts from neem seeds and T. pallida branches and leaves are similar to those observed by Souza & Vendramim (2000;, which indicated that these materials are effective for the control of eggs and nymphs of B. tabaci biotype B.…”
Section: Resultssupporting
confidence: 77%
“…The mortality percentages obtained with the extracts from neem seeds and T. pallida branches and leaves are similar to those observed by Souza & Vendramim (2000;, which indicated that these materials are effective for the control of eggs and nymphs of B. tabaci biotype B.…”
Section: Resultssupporting
confidence: 77%
“…The author has not attributed this fact to the action of the growth regulators present in the neem oil, but to the higher adherence of the product to the egg membrane, as observed with other vegetable oils. The ovicide effect of neem oil based products on phytophagous insects was also reported by Souza & Vendramim (2000).…”
Section: Survival and Duration Of Eggs And Larvae -Egg Sprayingmentioning
confidence: 62%
“…A parcela foi constituída por três folíolos de cada genótipo. O confinamento dos insetos deu-se em gaiolas de voil (15 cm x 5 cm), fechadas com velcro (Souza & Vendramim 2000). Adultos da mosca-branca (50 casais) foram aspirados da criação estoque e introduzidos na gaiola, onde permaneceram durante 24h para oviposição.…”
Section: Obtenção Dos Tomateirosunclassified